Elevated Serum Tsukushi Levels in Patients With Hyperthyroidism - Liu, Deying; Zhang, Peizhen; Wei, Xueyun; Deng, Yajuan; Liu, Wenhui; Guo, Dan; Liu, Jianfang; Xu, Bingyan; Huang, Chensihan; Huang, Junlin; Lin, Jiayang; Liu, Shiqun; et al. (Frontiers in Endocrinology, 2020)
Background: Tsukushi (TSK) is a secreted hepatokine recently identified as playing an important role in modulating glucose and lipid metabolism, and systemic energy homeostasis. However, information is not available regarding the association between circulating TSK and hyperthyroidism in humans. Methods: We measured serum TSK levels in 180 patients with hyperthyroidism and 82 healthy controls recruited from the clinic. Of them, 46 hyperthyroid patients received thionamide treatment for 3 months. Results: Hyperthyroid patients had higher levels of circulating TSK than healthy controls (186.67 (133.63-280.59) ng/ml vs.97.27 (77.87-146.96) ng/ml, P<0.001). Subjects with higher level of serum free triiodothyronine (T3) and free thyroxine (T4) had higher levels of circulating TSK. In addition, serum TSK levels markedly declined with the improvement of thyroid function after thionamide treatment. In multivariable linear regression analyses, circulating TSK concentrations were significantly associated with serum free T3, free T4, thyroid stimulating hormone, thyrotropin receptor antibody, total cholesterol, low-density lipoprotein cholesterol (LDL-cholesterol), high-density lipoprotein cholesterol (HDL-cholesterol), and basal metabolic rate (all P<0.01), adjusting for age, gender, smoking, and body mass index (BMI). Importantly, circulating TSK was significantly associated with risks of hyperthyroidism in multivariable logistic regression analyses, adjusting for age, gender, smoking, BMI, fasting glucose, LDL-cholesterol, and insulin resistance (HOMA-IR) [OR (95% CI), 1.012(1.005-1.019), P=0.001]. Conclusion: These findings indicate that circulating TSK concentrations are independently associated with hyperthyroidism, suggesting that circulating TSK may be a predictive factor of hyperthyroidism and can be used for therapeutic monitoring.